Ayamonte, Spanien - Marzoli, Dirce (e-Forschungsberichte des DAI, 2023)
In September 2013 an excavation was carried out at the Phoenician necropolis of Ayamonte, Hoya de los Rastros as part of the Phoenician studies of the DAI’s Madrid Department. The campaign was designed as a pilot phase for a long-term project in cooperation with the Delegación de Cultura de Huelva of the Junta de Andalucía. The aim of the project is to gain new insights into the life of the Phoenician settlers of the 8th and 7th century BC in the West through an interdisciplinary investigation of their tombs. The research complements the ongoing Tharsis-project of the DAI directed by Th. Schattner and J. A. Pérez Macías.